2015
DOI: 10.3109/19401736.2015.1089539
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of the translesion synthesis across abasic sites by mitochondrial DNA polymerase is low in mitochondria of 3T3 cells

Abstract: Translesion synthesis by specialized DNA polymerases is an important strategy for mitigating DNA damage that cannot be otherwise repaired either due to the chemical nature of the lesion. Apurinic/Apyrimidinic (abasic, AP) sites represent a block to both transcription and replication, and are normally repaired by the base excision repair (BER) pathway. However, when the number of abasic sites exceeds BER capacity, mitochondrial DNA is targeted for degradation. Here, we used two uracil-N-glycosylase (UNG1) mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…The authors also speculated that TFAM might not inhibit DNA repair in vivo (66). Our observation that TFAM promotes strand cleavage at AP sites suggests an active role of TFAM in processing ubiquitous AP sites, which may account for the rapid DNA depletion resulting from mitochondrial AP sites (36). Such strand cleavage activity may also act redundantly with APE1 or bifunctional glycosylases in their strand-scission activities.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The authors also speculated that TFAM might not inhibit DNA repair in vivo (66). Our observation that TFAM promotes strand cleavage at AP sites suggests an active role of TFAM in processing ubiquitous AP sites, which may account for the rapid DNA depletion resulting from mitochondrial AP sites (36). Such strand cleavage activity may also act redundantly with APE1 or bifunctional glycosylases in their strand-scission activities.…”
Section: Discussionmentioning
confidence: 83%
“…TFAM Promotes Strand Cleavage at AP Sites. Previous work has shown that mtDNA elimination counteracts the mutagenicity of AP sites in human and mouse cells, as evidenced by a decline in mtDNA copy number and a moderate mutation load after the induction of mitochondrial AP sites (36). Nonetheless, the chemical and molecular basis of AP-DNA elimination remains an important unsolved question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to "C-rule" the loss of adenines in mtDNA would give rise A→G transitions, while the loss of guanines would be non-mutagenic (Zhang et al 2006). However, recent study demonstrated that enzymatically created AP sites in mtDNA of mouse cells are weakly mutagenic, and that repair and DNA degradation occur more often than TLS of AP sites (Kozhukhar et al 2016). More studies are required to identify a possible origin of A H →G H transitions in mtDNA.…”
Section: A Hypothesis On the Origin Of Mtdna Mutationsmentioning
confidence: 99%
“…These isoforms derive from transcription from two distinct start sites as well as from alternative splicing of the mRNAs transcribed from the ung gene [5]. The role of UNG1 in the processing of uracil at mitochondria is not well defined and needs additional studies [6,7]. UNG2 is the nuclear DNA glycosylase [8] and its turnover is regulated by cell-cycle specific phosphorylations by cyclin-dependent kinases [9,10] and by a TP53-dependent phosphatase [9,10].…”
Section: The Family Of the Udgsmentioning
confidence: 99%